The Urgency Of Studying Philosophy And Its Scope - Zidna Fahma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The aim of this research is to explain the importance of studying philosophy, scope, figures and branches of philosophy. This research is a type of library research, research whose object of study uses a bibliography in the form of books, journals, articles as data sources. The characteristics of philosophical thinking are: descriptive, critical and analytical, evaluative or normative, speculative and systematic. So, philosophy can generally be interpreted as a science that investigates everything that exists to obtain the ultimate truth. The scope of philosophy is logic, aesthetics, ethics and metaphysics